Analisis Penerapan Corporate Social Responsibility pada PT. BPRS Puduarta Insani Berdasarkan Perspektif Maqashid Syariah - Siregar, Zaini Abdillah; Nasution, Annio Indah Lestari; Nasution, Muhammad Lathief Ilhamy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Corporate Social Responsibility is one form of the company's efforts to foster good relations with the community. Even though basically the company's activities are only for profit and operate for the benefit of shareholders, the company must pay attention to the community in its business activities. In the view of Islam, CSR is a company's obligation that is excluded from income that falls on the obligation of zakat, infaq and alms. So the problem being studied is how to implement Maqashid sharia in the CSR program at PT. BPRS Puduarta Insani and lies in the extent to which the CSR program is realized in operational activities. The methodology used in this study is a descriptive qualitative approach. The type of data used in this research is primary and secondary data. Based on the results of research conducted at PT. BPRS Puduarta Insani can be concluded that the implementation of corporate social responsibility has been going well. If viewed from maqashid sharia regarding the implementation of corporate social responsibility, it can be seen from programs such as orphan compensation, mosque construction assistance, achievement scholarships, and other social activities. So it can be concluded that the implementation of corporate social responsibility by PT. BPRS Puduarta Insani in accordance with the five concepts of maqashid sharia. Keywords: Corporate Social Responsibility, Maqashid Syariah, and PT. BPRS Puduarta Insani